Two new Gobiid fishes of the genus Eviota from the Indian Ocean (Teleostei: Gobiidae) - Greenfield, David W.; Jewett, Susan L. (Zootaxa, 2012)
Two new species from the Indian Ocean are described, Eviota notata and Eviota springeri. Eviota notata has a completecephalic sensory pore system (pattern 1), a dorsal/anal fin-ray formula of 7/7, some branched pectoral-fin rays, and threeprominent dark transverse marks on the nape. Eviota notata is known from the Seychelle Islands, Mauritius, and ChagosArchipelago. Eviota springeri lacks the IT pore belonging to cephalic sensory pore system pattern 2, has a dorsal/anal fin-ray formula of 8/7, unbranched pectoral-fin rays, and a small fifth pelvic-fin ray. Eviota springeri is known from the Sey-chelle Islands, Mauritius, Chagos Archipelago, and the Amirante Islands. An Errata concerning the type material of Eviota atriventris Greenfield & Suzuki is presented.